Intorno a "Gli Osservanti" di Franco Cordero - Condello, Angela (Teoria e Critica della Regolazione Sociale / Theory and Criticism of Social Regulation, 2024)
In this article I dig into Cordero’s theoretical work on the origins and phenomenology of legal norms. I aim to show that his focus on the archeology of the norms belongs to a tradition proper of a specific period of time, followed by other intellectuals (in France, for instance). Moreover I claim that his perspective could be fruitful today to value a peculiarly “human” way of conceiving the origin, the interpretation and the functionment of law and legal operations.